PENGGUNAAN AUDIO UNTUK PENGUATAN NOTASI MUSIK BRAILLE SEBAGAI MEDIA PEMBELAJARAN PADA MAHASISWA DISABILITAS NETRA - Muhamad Rafi Iman Widyanto; Firnando Sabetra, Firnando Sabetra (Universitas Negeri Padang, 2026)
This study aims to analyze the use of audio media as reinforcement in learning Braille music notation for visually impaired students at the Special Education Study Program of Universitas Negeri Padang. The research employed a quasi-experimental method with a pretest-posttest design to measure students’ understanding before and after the implementation of audio media. The subjects were visually impaired students learning basic Braille music notation. Data collection instruments included tests of Braille music notation reading skills. The results showed a significant improvement in students’ ability to understand Braille music notation symbols after using audio media as reinforcement. Audio media effectively assisted students in associating tactile Braille symbols with actual musical sounds, thereby enhancing conceptual understanding. Furthermore, the use of audio increased student engagement and learning independence. However, the study also identified limitations, including dependence on the quality of audio design and the need for initial guidance. In conclusion, audio media is effective as a reinforcement tool in learning Braille music notation and can serve as an innovative alternative to support multisensory learning for visually impaired students.